Autoimmunity Predisposition in Girls With Turner Syndrome - Wegiel, Malgorzata; Antosz, Aleksandra; Gieburowska, Joanna; Szeliga, Kamila; Hankus, Magdalena; Grzybowska-Chlebowczyk, Urszula; Wiecek, Sabina; Malecka-Tendera, Ewa; Gawlik, Aneta (Frontiers in Endocrinology, 2019)
Background: Turner Syndrome is associated with an increased risk of autoimmune diseases, such as autoimmune thyroiditis, coeliac disease, type 1 diabetes mellitus, inflammatory bowel disease, alopecia areata, or vitiligo. The presence of isochromosome iXq and exposure to estradiol may contribute to the development of the autoimmune process. The aim of this study was to determine the prevalence of autoimmune diseases in a group of TS patients and to assess the impact of karyotype and puberty on the development of autoimmune diseases. Patients & Methods: The analysis encompassed clinical and biochemical data of 134 patients treated between 2001 and 2018. All the patients were examined for autoimmune disease symptoms and tested for the presence of antithyroperoxidase (anti-TPO) and antithyreoglobulin (anti-TG) antibodies. In 73 of the patients, anti-transglutaminase (anti-tTG) antibodies were measured. Thyroid function was assessed by measuring TSH and fT4 levels. Results: The mean follow-up was 5.7± 3 years. An autoimmune disease was diagnosed in 46 (34.3%) patients: 39 (29.1%) had only one disorder, whilst 7 (5.2%) presented two disorders. The most common disorder, observed in 40 (29.9%) patients, was thyroid autoimmunity. Hashimoto disease was diagnosed in 20 (14.9%) patients. Of the 73 patients tested for coeliac disease, 4 (5.5%) had anti-tTG and 2 (2.7%) presented overt coeliac disease. Vitiligo was diagnosed in 3 (2.2%) patients, type 1 diabetes mellitus or psoriasis were diagnosed in 2 (1.5%) patients each, whilst alopecia areata or lichen sclerosus were diagnosed in 1 (0.7%) patient each. The impact of karyotype or estradiol exposure on developing autoimmune diseases were not statistically significant. Conclusions: Our study showed a higher incidence of autoimmune diseases in TS, which is in line with the literature; however, the impact of iXq, or spontaneous / inducted puberty was not confirmed.